Comfort ratings of hearing protection devices among chemical manufacturing plant workers who use radio communication - Rikhotso, O (Occupational Health Southern Africa, 2025)
Background:Personal protective equipment (PPE), including hearing protection devices (HPDs), can minimise the adverse health impacts of occupational exposures when properly designed, selected, used, and maintained. Wearer acceptance, compatibility with other protective clothing, and environmental conditions affect the use of PPE. The selection of HPDs should consider wearer comfort and the need for effective radio communication to increase field usage and effectiveness, in addition to their attenuation capabilities.Objective:To assess the comfort rating of HPDs that are concurrently used with radio communication at three chemical manufacturing plants in South Africa.Methods:A mixed methods cross-sectional study design, incorporating field observations, a questionnaire survey, and noise measurements, was used. Visits to three chemical plants (A, B, and C) involved 1) noise level measurements, 2) the collection of HPDs in use, and 3) administration of a questionnaire, which was designed to elicit information about workers’ subjective rating of comfort (isolation and radio communication) when using the devices. Data were analysed, descriptively, using Stata V13.Results:Average noise levels were highest in plant C, followed by plants A and B. Nineteen different HPDs were used across the three chemical plants. All were designed for effective attenuation against medium and high frequencies, but only nine were designed for effective attenuation across all frequencies. Fifty-four workers completed the questionnaire, 15 (27.8%) of whom felt completely isolated when using HPDs. Twenty-five (46.3%) rated radio communication as bad when using HPDs.Conclusion:The feeling of isolation and the quality of radio communication is subjective, varies amongst workers, and is influenced by both the spectral noise characteristics of the plant and the HPD used. To promote usage of HPDs and minimise the feeling of isolation and discomfort, the selection of devices should take the radio communication needs of workers into account.